Functional Interchangeability of Nucleotide Sugar Transporters URGT1 and URGT2 Reveals That urgt1 and urgt2 Cell Wall Chemotypes Depend on Their Spatio-Temporal Expression - Celiz-Balboa, Jonathan; Largo-Gosens, Asier; Parra-Rojas, Juan Pablo; Arenas-Morales, Verónica; Sepulveda-Orellana, Pablo; Salinas-Grenet, Hernán; Saez-Aguayo, Susana; Orellana, Ariel (Frontiers in Plant Science, 2020)
Nucleotide sugar transporters (NSTs) are Golgi-localized proteins that play a role in polysaccharide biosynthesis by transporting substrates (nucleotide sugars) from the cytosol into the Golgi Apparatus. In Arabidopsis, there is an NST subfamily of six members, called URGTs, which transport UDP-Rhamnose and UDP-Galactose in vitro. URGTs are very similar in protein sequences and, among them, URGT1 and URGT2 are highly conserved in protein sequence and also showed very similar kinetic parameters towards UDP-Rhamnose and UDP-Galactose in vitro. Despite the similarity in sequence and in vitro function, mutants in urgt1 led to a specific reduction in galactose in rosette leaves. In contrast, mutants in urgt2 showed a decrease in rhamnose content in soluble mucilage from seeds. Given these specific and quite different chemotypes, we wonder whether the differences in gene expression could explain the observed differences between the mutants. Towards that end, we analyzed whether URGT2 could rescue the urgt1 phenotype and vice versa by performing a promoter swapping experiment. We analyzed whether the expression of the URGT2 coding sequence, controlled by the URGT1 promoter, could rescue the urgt1 rosette phenotype. A similar strategy was used to determine whether URGT1 could rescue the urgt2 mucilage phenotype. Expression analysis of the swapped genes, using qRT-PCR, were similar to the native URGT1 and URGT2 genes in wild-type plants. To monitor the protein expression of the swapped genes, both URGTs were tagged with GFP. Confocal microscopy analyses of the swapped lines containing URGT2-GFP showed fluorescence in motile dot-like structures in rosette leaves. Swapped lines containing URGT1-GFP showed fluorescence in dot-like structures in the seed coat. Finally, the expression of URGT2 in urgt1 mutants rescued the Galactose reduction in rosette leaves. In the same manner, the expression of URGT1 in urgt2 mutants recovered the content of rhamnose in soluble mucilage. Hence, our results showed that their expression in different organs modulates the role in vivo of URGT1 and URGT2. Likely, this is due to their presence in different cellular contexts, where other proteins, acting in partnership, may drive their functions towards different pathways.